Digital Competitiveness and Poverty Index Quadrant: Mapping the Digital Public Administration Challenge (Evidence from Indonesia) - Wahyunengseh, Rutiana D; Hastjarjo, Sri (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2023)
The role of the internet in reducing poverty has been tested in several countries. However, according to bibliometric analysis, not much has been studied from the perspective of inclusive digital public administration. This research's novelty is to complements the digital governance research by analyzing the relationship between digital competitiveness and poverty rates in Indonesia. This study aims to map the challenges of developing digital governance in Indonesia in the context of promoting sustainable development and more inclusive society. The research method uses descriptive quantitative with quadrant analysis techniques. The data used are the poverty rate from the Indonesian Central Bureau of Statistics in 2021 and the Digital Competitiveness Index. The results of the study show: (i) there is a digital divide or digital poverty that contributes to the Digital Competitiveness gap; (i) the behavior of digital users for productivity is still low but shows an increase from the previous year. In conclusion, digital development must be designed to pursue inclusive and pro-poor development, supported by productive human resources. Further research is recommended to examine the correlation between components of the digital development index and the components of the poverty index to build model of inclusive digital public administration.